Writing a Research Paper for Journal of Nepal Agricultural Research Council - Joshi, Bal Krishna; Gurung, Tek Bahadur; Shrestha, Jiban; Upreti, Hari Krishna (Journal of Nepal Agricultural Research Council, 2018)
Agricultural research findings are required to reach soon to the farmers, extensionists, media, researchers, policy makers, businessperson, students, teachers and so many other stakeholders. Among different types of publications, research paper is generally published in journal considered as standard type of publication in term of quality and recognition. Most of the journals follow similar pattern and framework; however, the style, format and process may be different with each other. A research (scientific) paper is a written describing original research result using standard methods and materials. The major sections in a journal paper are abstract, introduction, materials and methods, results, discussion, conclusion, and references. Accordingly Journal of Nepal Agricultural Research Council has its own style and format. Author needs to follow guidelines strictly on the use of punctuation marks such as comma (,), period (.), space, justification etc; otherwise submitted manuscripts could be immediately return to author without considering in review process. In general, we received manuscripts with many errors on citation and references, poor elaboration of results of experiments, weak discussion, missing to acknowledge funding agencies, submitting non-editable figures, very few numbers of citations of Nepalese researchers, statements not in logical order, etc. In general, the scientific papers should be written in simple way with new but sufficient justification backed up by data in the form of tables, graphs, flow diagrams etc so that readers can understand easily with high readability. The submitted manuscript in the journal office are sent to two to three reviewers for specific recommendation on the originality of the work, appropriateness of the approach and experimental design, adequacy of experimental techniques, soundness of conclusions and interpretations, relevance of discussion and importance of the research. The language clarity and organization of the article are also asked with the reviewers. In response to reviewer’s comments all authors are expected to reply each and every comments and suggestions of reviewers, if such comments and suggestion are not acceptable, the author/s can argue for their points, if genuine. Here in this paper we described detail contents of each section along with style and format for a research paper writing targeted to Journal of Nepal Agricultural Research Council.